TRP Channels and Pain - Cortright, Daniel N.; Szallasi, Arpad (Current Pharmaceutical Design, 2009)
Preclinical research has identified an array of ion channels in sensory neurons involved in the generation and transduction of pain as potential targets for pharmacological intervention. Paramount among these new targets is the family of thermosensitive transient receptor potential channels, referred to as “thermoTRPs”. We detect a wide range of noxious stimuli via a limited number (as of today, six) of thermoTRP channels, four of which (TRPV1-TRPV4) respond to heat and two (TRPA1 and TRPM8) are sensitive to cold. Targeting these thermoTRP channels represents a new and logical strategy in pain relief. Unlike traditional analgesic drugs that either suppress inflammation (e.g. NSAIDs and COX-2 inhibitors) or block pain transmission (e.g. opiates), TRP channel inhibitors aim to prevent pain by blocking a receptor where pain is generated. The archetypal thermoTRP is the vanilloid (capsaicin) receptor TRPV1. TRPV1 has a dynamic threshold of activation. Agents in inflammatory soup, including endogenous TRPV1 agonists (so-called “endovanilloids”), act in concert to reduce the heat activation threshold of TRPV1. In patients, the expression of TRPV1 is upregulated in a number of painful inflammatory disorders. TRPV1 as a pain target has been validated by genetic deletion and pharmacological inhibition experiments. This area of drug development has been moving rapidly. It took less than a decade from the cloning of TRPV1 to clinical trials with potent small molecule TRPV1 antagonists. This review evaluates current evidence that supports particular TRP channels as targets for novel analgesic drugs, along with potential adverse effects that may limit drug development.
Keywords: TRPA1